« Suivre la route ».Mobilités et échanges entre Mali, Mauritanie et Sénégal - Armelle Choplin; Jérôme Lombard (EchoGéo)
Fifty years after the independence of Senegal, Mali and Mauritania, the issue of regional integration and political relations between the three states is at stake. The ECOWAS promotes the establishment of a common market and free movement of people. This article sheds light on the spreading of transports networks, increasing exchanges and people transborder practices. Based on a multi-sited fieldwork along the “route”, this paper highlights new form of popular transnationalism but also the contradiction between Ecowas theoretical principles and the growing controls, which hinder circulation.